2019
DOI: 10.1017/s1478951519000531
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes towards the dying and death anxiety in acute care nurses – can a workshop make any difference? A mixed-methods evaluation

Abstract: ObjectivesIn Singapore, the core curriculum for end-of-life (EOL) care used in nurse training courses is limited. Only 45% of nurses indicated familiarity with inpatient palliative care. Nurses who lack skills in palliative care may develop anxiety and negative attitudes towards caring for dying patients. We explored whether a two-day, multimodal EOL care workshop could reduce nurses’ death anxiety and improve nurses’ skills, knowledge, and attitude towards palliative care.MethodsForty-five nurses participated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 26 publications
4
18
0
Order By: Relevance
“…According to the findings of the present study, it was determined that nurses who received terminal patient care training outside the undergraduate curriculum considered themselves more competent in the care of dying patients when compared with those who did not receive training. In the literature, various studies state that death education is effective in developing a positive attitude towards death, reducing death anxiety, and providing and developing effective interventions 27–29 . These results support our view that the quality, up‐to‐dateness, and continuity of education is very important for the nursing profession to provide quality service to the individual, family, and society.…”
Section: Discussionsupporting
confidence: 57%
“…According to the findings of the present study, it was determined that nurses who received terminal patient care training outside the undergraduate curriculum considered themselves more competent in the care of dying patients when compared with those who did not receive training. In the literature, various studies state that death education is effective in developing a positive attitude towards death, reducing death anxiety, and providing and developing effective interventions 27–29 . These results support our view that the quality, up‐to‐dateness, and continuity of education is very important for the nursing profession to provide quality service to the individual, family, and society.…”
Section: Discussionsupporting
confidence: 57%
“…For instance, the acceptance and commitment therapy might be a potential approach (Dereix-Calonge et al, 2019). Also, the workshop plan to improve students' skills, knowledge, and attitude toward palliative care for dying patients should be considered to be concluded in the training program, which has been evidenced to be useful for the reduction in students' anxiety and fear of death (Cheong et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In light of the information presented above, it is expected that one of the most important concerns experienced by nurses during the pandemic is death anxiety. Death anxiety is described as fear and anxiety about death triggered by thoughts of dying (Chen et al, 2020 ; Cheong et al, 2020 ). Death anxiety has been implicated in the development of many mental disorders (Menzies et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Death anxiety has been implicated in the development of many mental disorders (Menzies et al, 2019 ). Nurses with death anxiety may exhibit adverse reactions to caring for dying patients (Cheong et al, 2020 ). Some studies on death anxiety during the COVID-19 pandemic have shown that nurses have higher death anxiety than other healthcare professionals (Şahin et al, 2020 ; Tepe Medin et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%